Eutiposis and bacterial necrosis of the vine on the vineyards of the Odessa region - Kovaleva, I.; Konup, L.; Nikolaeva, N.; Konup, A.; Chistyakova, V. (Quarantine and plant protection, 2022)
Goal. The aim of the study was to identify bacterial necrosis and eutyposis of the vine in vineyards in the Odessa region and to identify the causative agents of these diseases. Methods. For this, a phytosanitary examination of vine plantations was carried out to identify the symptoms of these diseases. To identify the causative agent of bacterial necrosis — Xylophilus ampelinus, a serological method of enzyme-linked immunosorbent assay (ELISA) was used, for eutyposis, the causative agent of which is Eutypa lata — a molecular biological method of polymerase chain reaction (PCR) with gel electrophoretic detection. Results. As a result of a phytosanitary examination of vine plantations of various farms in the Odessa region, bushes of vine plants were found with characteristic symptoms of bacterial necrosis and eutyposis, namely, oppressed growth of shoots, small clusters or their absence, light brown necrosis was observed on the cross section of sleeves and boles. A non-seasonal change in the color of grape leaves, namely chlorosis, was noted. As a result of laboratory studies in plants with characteristic symptoms of diseases, the causative agents of bacterial necrosis and eutyposis of grapes were identified. Conclusions. As a result of a phytosanitary examination of vine plantations in the Odessa region, the presence of vine bushes with symptoms of bacterial necrosis and eutyposis was revealed. A small percentage of damage to vine bushes by the pathogen of bacterial necrosis and a significant defeat by the pathogen of eutiposis were established. Using the PCR method with gel electrophoretic detection, it was established that grape plants were affected by the causative agent of eutyposis. The causative agent of bacterial necrosis was identified by ELISA.